Need Analysis of The Development Discovery Learning-Based Module Assisted by PhET Simulations to Train Students' Conceptual Understanding - Fathiyah, Atika Nurul; Zulfarina, Zulfarina; Yennita, Yennita (FKIP - Universitas Riau, 2023)
Students' conceptual understanding is an essential component in terms of successful learning. But the fact shows that the conceptual understanding of Indonesian students is still relatively low. One of the factors for the unelevated understanding of the concept is the lack of active participation during the process. Student involvement encounter by using teaching materials that facilitate student learning independence. One way is to use a module integrated with discovery learning models that authorize students to learn independently. This research is survey research as an initial step in developing discovery learning-based learning modules assisted by PhET Simulations. The benefit of this research is to find out what students currently need in science learning and how much students need for the buildup of discovery learning-based modules. The subjects used in this study were junior high school students with a sample size of 35 students and 26 science teachers selected by region. The needs analysis includes four indicators, a) analysis of learning problems; b) student analysis; c) objective analysis; and d) learning setting analysis. Based on the results of this study, the discovery learning-based learning modules assisted by PhET Simulations needed to be developed as a science learning medium to train students' conceptual understanding in Riau and Riau Islands provinces.